2014
DOI: 10.1590/0100-2945-361/13
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de genótipos de bananeira no recôncavo da Bahia

Abstract: Objetivou-se com este trabalho avaliar o desempenho agronômico de genótipos tri- e tetraploides de bananeira, em dois ciclos de produção, visando a selecionar os mais promissores para recomendação de cultivo na região do Recôncavo da Bahia. O delineamento utilizado foi o de blocos casualizados, com 11 genótipos distribuídos em 3 blocos, com quatro plantas úteis por parcela, conduzidos em espaçamento de 3 m x 2 m. Analisaram-se os seguintes caracteres agronômicos: altura da planta (m); diâmetro do pseudocaule (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
(23 reference statements)
4
6
3
8
Order By: Relevance
“…These authors found the same variation in pseudostem height and pseudostem diameter between the first and second production cycles, with average pseudostem height values of 3.5-4.5 m and pseudostem diameter of 0.25-0.30 m, respectively. The yields were relatively higher or similar to those reported by Roque et al (2014) In relation to the time between transplanting and bunch harvest, a tendency to a shorter time may be observed in the second production cycle, as the humic substances dose is decreased to the minimum point of the quadratic model curve (Figure 1).…”
Section: Resultssupporting
confidence: 84%
“…These authors found the same variation in pseudostem height and pseudostem diameter between the first and second production cycles, with average pseudostem height values of 3.5-4.5 m and pseudostem diameter of 0.25-0.30 m, respectively. The yields were relatively higher or similar to those reported by Roque et al (2014) In relation to the time between transplanting and bunch harvest, a tendency to a shorter time may be observed in the second production cycle, as the humic substances dose is decreased to the minimum point of the quadratic model curve (Figure 1).…”
Section: Resultssupporting
confidence: 84%
“…The absolute means of PH, as well as PD, NL, and LAF (Table 3), were close to those reported by Roque et al (2014), who agronomically evaluated an irrigated cultivation of 'BRS Princesa' banana in the same region with the use of solid fertilization and without the use of humic substances.…”
Section: Resultssupporting
confidence: 85%
“…The absolute means of HY observed in this study, for the production variables, are higher than those reported by Roque et al (2014). According to the F test of the analysis of variance, the absolute means of HY, LCF, and DCF were statistically superior to the absolute means of the treatments without PE application (Table 5).…”
Section: Ph (Water)contrasting
confidence: 61%
“…Despite the wide range of varieties existing in Brazil, only a few cultivars have agronomic traits and fruit quality considered suitable for commercial exploitation (Roque et al 2014). In the Brazilian market, the main commercial cultivars are from the subgroups Cavendish (Nanica, Nanicão and Grand 1.…”
Section: Abstract Resumomentioning
confidence: 99%